Prevalence and associated factors of delay in seeking malaria treatment among under five children in the Horn of Africa: A systematic review and meta-analysis - Muluken Chanie Agimas; Mekuriaw Nibret Aweke; Berhanu Mengistu; Lemlem Daniel Baffa; Elsa Awoke Fentie; Ever Siyoum Shewarega; Aysheshim Kassahun Belew; Esmael Ali Muhammad (PLoS ONE, 2025)
Introduction Malaria is a global public health problem, particularly in sub-Saharan African countries. It is responsible for 90% of all deaths worldwide. To reduce the impact and complications associated with delayed treatment of malaria among children under five, comprehensive evidence about the magnitude and determinants of delayed treatment for malaria could be the solution. But there are no national-level studies in the Horn of Africa for decision-makers. Objective To assess the prevalence and associated factors of delay in seeking malaria treatment among under-five children in the Horn of Africa. Method Published and unpublished papers were searched on Google, Google Scholar, PubMed/Medline, EMBASE, SCOPUS, and the published articles’ reference list. The search mechanism was established using Medical Subject Heading (MeSH) terms by combining the key terms of the title. Joana Brigg’s Institute critical appraisal checklist was used to assess the quality of articles. A sensitivity test was conducted to evaluate the heterogeneity of the studies. The visual funnel plot test and Egger’s and Begg’s statistics in the random effect model were done to evaluate the publication bias and small study effect. The I2 statistics were also used to quantify the amount of heterogeneity between the included studies. Results The pooled prevalence of delayed treatment for malaria among under-five children in the Horn of Africa was 48% (95% CI: 34%–63%). History of child death (OR =2.5, 95% CI: 1.73–3.59), distance >3000 meters (OR = 2.59, 95% CI: 2.03–3.3), drug side effect (OR = 2.94, 95% CI: 1.86–4.67), formal education (OR = 0.69, 95% CI: 0.49–0.96), middle income (OR = 0.42, 95% CI: 0.28–0.63), expensiveness (OR = 4.39, 95% CI: 2.49–7.76), and affordable cost (OR = 2.13, 95% CI: 1.41–3.2) for transport were factors associated with malaria treatment delay among children. Conclusion and recommendations About one out of two parents in the Horn of Africa put off getting their kids treated for malaria. High transportation expenses, long travel times (greater than 3,000 meters) to medical facilities, and anxiety about drug side effects were major risk factors that contributed to this delay. On the other hand, a middle-class income was found to be protective of treatment delays. These results highlight how crucial it is to improve access to healthcare services, both financially and physically, to minimize delays in treating malaria in the area’s children.